1951. Nephrotoxicity Associated With Imipenem/Cilastatin/Relebactam (IMI/REL) vs. Imipenem/Cilastatin Plus Colistin (IMI+CST) in Patients With Imipenem-Nonsusceptible (NS) Bacterial Infections. (26th November 2018) - Brown, Michelle; Motsch, Johann; Kaye, Keith; File, Thomas; Boucher, Helen W; Vendetti, Neika; Aggrey, Angela; Joeng, Hee-Koung; Tipping, Robert; Du, Jiejun; Depestel, Daryl D; Butterton, Joan; et al.
Abstract: Background: Nephrotoxicity is a common complication of CST-based therapy, limiting its use to treat carbapenem-resistant bacterial infections. REL is a novel β-lactamase inhibitor that restores imipenem activity against many imipenem-NS strains of Gram-negative pathogens. IMI/REL was shown to be as effective but better tolerated than IMI+CST in the phase 3 RESTORE-IMI 1 study (NCT02452047), including a lower incidence of treatment-emergent nephrotoxicity (prespecified secondary endpoint). Here we present additional renal safety data from that trial. Methods: Randomized, active-controlled, double-blind, phase 3 trial in adults with infections caused by ≥1 imipenem-NS (but CST- and IMI/REL-susceptible) pathogen. Treatment (2:1) was IMI/REL or IMI+CST for 5–21 days in complicated intra-abdominal infection and complicated urinary tract infection and 7–21 days in hospital-acquired/ventilator-associated bacterial pneumonia. For baseline serum creatinine (Cr) <1.2 mg/dL, nephrotoxicity was defined as a doubling of serum Cr to >1.2 mg/dL OR decrease in Cr clearance [CrCl] ≥50%; for Cr ≥1.2 mg/dL, nephrotoxicity was defined as an increase in serum Cr ≥1 mg/dL OR decrease from baseline in CrCl ≥20% OR need for renal replacement therapy. KDIGO and RIFLE criteria of acute kidney injury (AKI) were applied to the data; renal-related adverse events (AEs) were analyzed. Results: A total of 47 patients were randomized, treated (31 IMI/REL, 16 IMI+CST), and included in this analysis. A significantly smaller percentage of patients in the IMI/REL than the IMI+CST group experienced protocol-defined nephrotoxicity (% difference: −45.9 [95% CI: −69.1, −18.4]; P = 0.002) during study treatment and the 14-day follow-up period (table). These results were confirmed by applying KDIGO and RIFLE criteria, with no patients in the IMI/REL group in stage 3 AKI or failure compared with 31.3% and 25.0%, respectively, in the IMI+CST group. Fewer renal AEs, including discontinuations due to renal events, were observed in the IMI/REL group. Conclusion: IMI/REL demonstrates a more favorable renal safety profile compared with CST-based therapy, as demonstrated by a lower incidence of treatment-emergent nephrotoxicity and AKI with IMI/REL across several different analyses. Disclosures: M. Brown, Merck & Co., Inc.: Employee, Salary. J. Motsch, Heidelberg University: Research Contractor, Research grant. K. Kaye, Merck & Co., Inc.: Consultant and Research Contractor, Research grant. Melinta, Achaogen, Allergan: Consultant, Consulting fee. T. File, Bio Merieux, Curetis, Melinta, Merck, MotifBio, Nabriva, Paratek, Pfizer: Consultant, Consulting fee. H. W. Boucher, Merck & Co., Inc.: Scientific Advisor, Consulting fee. N. Vendetti, Merck & Co., Inc.: Employee, Salary. A. Aggrey, Merck & Co., Inc.: Employee, Salary. H. K. Joeng, Merck & Co., Inc.: Employee, Salary. R. Tipping, Merck & Co., Inc.: Employee, Salary. J. Du, Merck & Co., Inc.: Employee, Salary. D. D. Depestel, Merck & Co., Inc.: Employee, Salary. J. Butterton, Merck & Co., Inc.: Employee, Salary and Stock. N. A. Kartsonis, Merck & Co., Inc.: Employee, Salary and Stocks. A. Paschke, Merck & Co., Inc.: Employee and Shareholder, Salary.